Anthropogenic Mixing in Seasonally Stratified Shelf Seas by Offshore Wind Farm Infrastructure - Robert M. Dorrell; Charlie J. Lloyd; Ben J. Lincoln; Tom P. Rippeth; John R. Taylor; Colm-cille P. Caulfield; Jonathan Sharples; Jeff A. Polton; Brian D. Scannell; Deborah M. Greaves; Rob A. Hall; John H. Simpson (Frontiers in Marine Science, 2022)
The offshore wind energy sector has rapidly expanded over the past two decades, providing a renewable energy solution for coastal nations. Sector development has been led in Europe, but is growing globally. Most developments to date have been in well-mixed, i.e., unstratified, shallow-waters near to shore. Sector growth is, for the first time, pushing developments to deep water, into a brand new environment: seasonally stratified shelf seas. Seasonally stratified shelf seas, where water density varies with depth, have a disproportionately key role in primary production, marine ecosystem and biogeochemical cycling. Infrastructure will directly mix stratified shelf seas. The magnitude of this mixing, additional to natural background processes, has yet to be fully quantified. If large enough it may erode shelf sea stratification. Therefore, offshore wind growth may destabilize and fundamentally change shelf sea systems. However, enhanced mixing may also positively impact some marine ecosystems. This paper sets the scene for sector development into this new environment, reviews the potential physical and environmental benefits and impacts of large scale industrialization of seasonally stratified shelf seas and identifies areas where research is required to best utilize, manage, and mitigate environmental change.

Control of a phytoplankton bloom by wind‐driven vertical mixing and light availability - Joanne E. Hopkins; Matthew R. Palmer; Alex J. Poulton; Anna E. Hickman; Jonathan Sharples (Limnology and Oceanography, 2021)
The balance of physical and biological processes governing phytoplankton growth rates and the accumulation of biomass is widely debated in the literature, notably during the winter–spring transition. Here we show, in a temperate shelf sea that variability in the depth of the actively mixing surface layer is the leading order control. During a 2‐week period preceding the peak of the spring bloom we observe two distinct regimes; first, growth within the euphotic zone during the day and re‐distribution of new biomass to the seasonal pycnocline at night by convective mixing; then, more rapid biomass accumulation trapped within a shallower, wind‐driven actively mixing layer that was decoupled from the pycnocline below. Our observations of the bloom in the Celtic Sea, Northwest European Shelf, were made using ocean gliders and include measurements of the dissipation of turbulent kinetic energy. A 1‐D phytoplankton growth model driven by our measurements of dissipation and incident irradiance replicates the observed bloom and reinforces the conclusion that physical processes that mediate light availability were key. Day‐to‐day variability in cloud cover and the ability of phytoplankton to acclimate to their light environment were also important factors in determining growth rates, and the timing of the biomass peak. Our results emphasize the need for accurate turbulent mixing parameterizations in coupled hydrodynamic‐ecosystem models. Our findings are applicable to any region where wind‐driven mixing can modify nutrient and light availability, especially across subpolar shelves in the northern hemisphere where light rather than nutrients is typically the limiting factor on phytoplankton growth.

Variability of internal tide energy, mixing and nitrate fluxes in response to changes in stratification on the northeast New Zealand continental shelf - Jonathan Sharples; John R. Zeldis (New Zealand Journal of Marine and Freshwater Research, 2021)
A 4‐month time series of water column temperature structure on the shelf of North Island New Zealand is used to calculate the energy in the internal tide as stratification evolved between spring and summer. Average total energy in the internal tidal wave was 200 J m −2 , with peaks reaching 600 J m −2 . Wave energy was weakly correlated with stratification ( r = 0.2) and with the spring‐neap cycle of tidal currents ( r = 0.17). Overall there was little predictability in internal tide behaviour in response to the physical environment. Reduction in wave energy was associated with a downwelling‐favourable wind event which reduced stratification by mixing and by removing deeper water off the shelf. Vertical eddy diffusivity driven by internal wave dissipation ranged between 5.6 × 10 −5 and 3.2 × 10 −4 m 2 s −1 . Combined with nitrate data this diffusivity resulted in diapycnal nitrate fluxes towards the sea surface of 1.6–2.2 mmol m −2 day −1 . Strong stratification in summer reduced the eddy diffusivity but had little effect on nitrate flux as a strengthened vertical nitrate gradient compensated for the reduced diffusivity. This compensation will be important when predicting how stronger stratification in a warmer climate might alter diapycnal nutrient supplies to the upper ocean.

Short-term and seasonal variation in metabolic balance in Liverpool Bay - Anouska Panton; Claire Mahaffey; Naomi Greenwood; Joanne Hopkins; David Montagnes; Jonathan Sharples (Ocean Dynamics, 2012)

Distribution and chromatic adaptation of phytoplankton within a shelf sea thermocline - Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Jonathan Sharples; Vladimir Krivtsov; Matthew R. Palmer (Limnology and Oceanography, 2009)
Observations of vertical gradients in phytoplankton community structure were made through the water column of the seasonally stratified Celtic Sea, including within the thermocline. A deep chlorophyll maximum (DCM) was located within the thermocline at all stations, coupled to the nitracline. Vertical gradients in phytoplankton community composition were routinely observed within the thermocline. The cell abundance maxima for Synechococcus occurred in the upper part of the DCM coincident with a picoeukaryote abundance minima. Picoeukaryote abundance typically increased at or just above the peak of the DCM. Diatoms were observed occasionally at the DCM peak. Pigment compositions and phytoplankton absorption spectra indicated that the different phytoplankton communities were chromatically well adapted to the spectral composition of irradiance at the depths where they occurred in the water column. Profiles of vertical eddy diffusivity revealed that timescales formixing between the phytoplankton layers within the thermocline were in excess of typical phytoplankton growth rates. The observed vertical gradients in community structure could therefore result from selection and niche partitioning of phytoplankton types on the light and nutrient gradient within the thermocline. The data further indicate that the pigments, light absorption characteristics, and cell size contribute to the phytoplankton selection process.

Summer heatwaves promote blooms of harmful cyanobacteria - KLAUS D. JÖHNK; JEF HUISMAN; JONATHAN SHARPLES; BEN SOMMEIJER; PETRA M. VISSER; JASPER M. STROOM (Global Change Biology, 2008)
Dense surface blooms of toxic cyanobacteria in eutrophic lakes may lead to mass mortalities of fish and birds, and provide a serious health threat for cattle, pets, and humans. It has been argued that global warming may increase the incidence of harmful algal blooms. Here, we report on a lake experiment where intermittent artificial mixing failed to control blooms of the harmful cyanobacterium Microcystis during the summer of 2003, one of the hottest summers ever recorded in Europe. To understand this failure, we develop a coupled biological–physical model investigating how competition for light between buoyant cyanobacteria, diatoms, and green algae in eutrophic lakes is affected by the meteorological conditions of this extreme summer heatwave. The model consists of a phytoplankton competition model coupled to a one‐dimensional hydrodynamic model, driven by meteorological data. The model predicts that high temperatures favour cyanobacteria directly, through increased growth rates. Moreover, high temperatures also increase the stability of the water column, thereby reducing vertical turbulent mixing, which shifts the competitive balance in favour of buoyant cyanobacteria. Through these direct and indirect temperature effects, in combination with reduced wind speed and reduced cloudiness, summer heatwaves boost the development of harmful cyanobacterial blooms. These findings warn that climate change is likely to yield an increased threat of harmful cyanobacteria in eutrophic freshwater ecosystems.

Spring‐neap modulation of internal tide mixing and vertical nitrate fluxes at a shelf edge in summer - Jonathan Sharples; Jacqueline F. Tweddle; J. A. Mattias Green; Matthew R. Palmer; Young-Nam Kim; Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Tom P. Rippeth; John H. Simpson; Vladimir Krivtsov (Limnology and Oceanography, 2007)
Measurements of the intra‐tidal and spring‐neap variation in the vertical flux of nitrate into the base of the sub‐surface chlorophyll maximum (SCM) were made at the shelf edge of the Celtic Sea, a region with strong internal mixing driven by an internal tide. The neap tide daily mean nitrate flux was 1.3 (0.9‐1.8, 95% confidence interval) mmol m ‐2 d ‐1 . The spring tide flux was initially estimated as 3.5 (2.3‐5.2, 95% confidence interval) mmol m ‐2 d ‐1 . The higher spring tide nitrate flux was the result of turbulent dissipation occurring within the base of the SCM as compared to deeper dissipation during neap tides and was dominated by short events associated with the passage of internal solitons. Taking into account the likely under‐sampling of these short mixing events raised the spring tide nitrate flux estimate to about 9 mmol m ‐2 d ‐1 . The neap tide nitrate flux was sufficient to support substantial new production and a considerable fraction of the observed rates of carbon fixation. Spring tide fluxes were potentially in excess of the capacity of the phytoplankton community to uptake nitrate. This potential excess nitrate flux during spring tides may be utilized to support new production during the lower mixing associated with the transition toward neap tide. The shelf edge is shown to be a region with a significantly different phytoplankton community as compared to the adjacent Celtic Sea and northeast Atlantic Ocean, highlighting the role of gradients in physical processes leading to gradients in ecosystem structure.

Quantifying turbulent mixing and oxygen fluxes in a Mediterranean-type, microtidal estuary - Jonathan Sharples; Michael J. Coates; John E. Sherwood (Ocean Dynamics, 2003)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

Tidal currents, mean flows, and upwelling on the north‐east shelf of New Zealand - Jonathan Sharples; Malcolm J. N. Greig (New Zealand Journal of Marine and Freshwater Research, 1998)
Continuous time‐series of near‐bed and near‐surface currents and temperature were recorded, at the shelf edge and on the shelf of northeast New Zealand, between June 1994 and January 1996. Tidal analysis of the current records show that typical tidal currents in the region are dominated by the Mj constituent, with amplitudes between 5 and 10 cm s ‐1 . The amplitude of the M 2 tide varies in response to the existence of an internal tide, and the tide was also found to include higher harmonics of the M 2 tide during periods of strong internal tide activity. These higher harmonics are likely to be the result of a non‐linear internal tide. Mean flows at the surface throughout the records were generally parallel to the bathymetry and towards the southeast, with typical speeds of between 20 and 30 cm s ‐1 , sometimes reaching 60 cm s ‐1 near Cape Brett. It is suggested that flow curvature around Cape Brett could be a significant localised upwelling mechanism. Near‐bed currents showed a strong cross‐shelf component in response to along‐shelf wind stress, indicating episodic wind‐driven upwelling events driving slope water onto the shelf between the autumnal and vernal equinoxes. It is estimated that such upwelling introduces a net supply of 10 ± 3 mmol m ‐3 of nitrate to the shelf waters between Cape Brett and Hauraki Gulf.

Data buoy measurements of phytoplankton dynamics in southampton water, UK, a temperate latitude estuary with high nutrient inputs - Paul N. Wright; David J. Hydes; Mary Lou Lauria; Jonathan Sharples; Duncan A. Purdie (Ocean Dynamics, 1997)